Internet-based hedonic indices of rents and prices for flats: Example of Berlin - Konstantin A. Kholodilin; Andreas Mense (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
In this paper, we suggest to estimate the home rents and prices in German regions/cities using the data from Internet ads offering the housing for rent and sale. Given the richness of information contained in the ads, we are able to construct the quality-adjusted rent and price indices using the hedonic approach. The results can be applied both for investigating the dynamics of rents/prices and for examining their distribution by city districts or regions.
Keywords: C21; O47; R11; 330; Internet ads; home rents; home prices; German regions; Berlin; hedonic approach